مسؤولية مقدم الخدمة في القانون الجزائري - أحمد, ذهب (جامعة الوادي.University eloued, 2021)
"يعتبر التفاعل بين مقدم الخدمة والمستهلك الركيزة الأساسية لبناء علاقة قوية ودائمة بين المنظمة والمستهلك، لأنه يعطي ميول واعتمادية كبيرة للعميل باتجاه المنظمة وخدماتها، بالقدر الذي يجعل هذا المستهلك يشعر وكأن المنظمة هي الأمل الوحيد الذي يمكنه من تحقيق رغباته ويستجيب لطموحاته بأكثر فعالية ومصداقية. وإن تقديم خدمة جيدة للمستهلكين يؤدي بالمنظمة إلى تحقيق الجودة في أداء الخدمة، حيث لا بد من وجود لغة مشتركة وتفهم وعمل جماعي لتحقيق الجودة في خدمة المستهلك وهذا يعني أن يكون مناخ العمل في المنظمة يمكن من تحقيق الجودة في أداء الخدمة، أي أن القيم التي يتبناها الأفراد والممارسات اليومية التي يتعودون إراديا عليها، والعنصر البشري هو القدوة التي تمكن من تحقيق التفوق في مجال العمل الخدمي. ""Summary: The interaction between the service provider and the consumer is the basic foundation for building a strong and lasting relationship between the organization and the consumer, because it gives great tendencies and reliability to the customer towards the organization and its services, to the extent that this consumer feels as if the organization is the only hope that enables him to achieve his desires and respond to his ambitions more effectively and credibly. Providing good service to consumers leads the organization to achieve quality in service performance, as there must be a common language, understanding and teamwork to achieve quality in consumer service. This means that the work environment in the organization enables quality in service performance, meaning that the values it adopts Individuals and daily practices that they are voluntarily accustomed to, and the human element is the role model that enables achieving excellence in the field of service work. "
ماستر قانون أعمال
Keywords: مقدم الخدمة- المستهلك